Advances in Services Innovations
DOI: 10.1007/978-3-540-29860-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Service Engineering in Action: The Palm/Erlang-A Queue, with Applications to Call Centers

Abstract: Our note1 is dedicated to the Palm/Erlang-A Queue. This is the simplest practiceworthy queueing model, that accounts for customers' impatience while waiting. The model is gaining importance in support of the staffing of call centers, which is a central step in their Service-Engineering. We discuss computations of performance measures, both theoretical and software-based (via the 4CallCenter software). Then several examples of Palm/Erlang-A applications are presented, mostly motivated by and based on real call … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 19 publications
0
110
0
Order By: Relevance
“…In fact, a recent empirical study by Brown et al (2005) based on call center data, found that service times have a distribution which is "closer" to a lognormal, not in line with the prevalent exponential assumption. Interestingly, Mandelbaum and Zeltyn (2005) observe that the performance predicted by the Erlang A formulae are fairly close to observed performance despite the various sources of misspecification. This is consistent with the performance-based approach advocated here.…”
Section: A Call Center Staffing Problemmentioning
confidence: 53%
“…In fact, a recent empirical study by Brown et al (2005) based on call center data, found that service times have a distribution which is "closer" to a lognormal, not in line with the prevalent exponential assumption. Interestingly, Mandelbaum and Zeltyn (2005) observe that the performance predicted by the Erlang A formulae are fairly close to observed performance despite the various sources of misspecification. This is consistent with the performance-based approach advocated here.…”
Section: A Call Center Staffing Problemmentioning
confidence: 53%
“…More recently, mainly triggered by the application area of the call-center industry, more authors have studied queueing models with abandonments [see e.g. Garnett et al (2002) and Mandelbaum et al (2002); Mandelbaum and Zeltyn (2007) and references therein].…”
Section: Discrete-time Models With Abandonmentsmentioning
confidence: 99%
“…Mandelbaum and Zeltyn (2007)]. This continuous-time queueing model is a variant of the well-known M/M/c model.…”
Section: A Discrete-time Delay Queueing Model With Abandonmentsmentioning
confidence: 99%
“…Palm [10,11] (cited in [8] and [12]) derived the probability of abandonment and the mean waiting time for an arbitrary customer. (It is mentioned in [9, p. 169] that Engset's main model in his report from 1915 under certain conditions is identical to Palm's model.)…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of the waiting time is shown in such books as Gnedenko and Kovalenko [4, p. 64] and Riordan [12, p. 109]. Lately, this system has been used widely as a basic model for the performance evaluation of a call center [8,15]. The author [13] recently presented a detailed analysis of the waiting time in the M/M/m/(m + c) queue (with a finite waiting room) with impatient customers.…”
Section: Introductionmentioning
confidence: 99%